PHÂN TÍCH DI TRUYỀN KHẢ NĂNG DI CHUYỂN THEO PHENANTHRENE CỦA VI KHUẨN PSEUDOMONAS STUTZERI E1 - Oanh, Nguyễn Thị Phi; Springael, Dirk; Nielsen, Line; Santos, Paulina Estrada De Los; Mot, René De (Tạp chí Khoa học Đại học Cần Thơ, 2008)
ABSTRACT Pseudomonas stutzeri strain E1 shows a two-time accelerated swarming behavior in minimal medium with sprayed phenanthrene in swimming assays and a five-time higher chemotaxis towards dissolved phenanthrene in capillary assays. A mutant bank of strain E1 was constructed using the pTnMod-OGm plasposon mutagenesis system. 82 out of 2639 electroporants screened showed an altered phenotype of phenanthrene-driven motility and/or phenanthrene degradation. 16 representative mutants were selected for sequencing the genes flanking the plasposon insertion. Mutations in flhA resulted in abolished swimming and swarming phenotype, and in flgK resulted in abolished swimming and diminished swarming phenotype. A mutation in cheY performed abolished swimming and reduced swarming activity while a gidA mutation resulted in decreased phenanthrene degradation and both decreased swimming and swarming behavior. A mutation in gene encoding a Zn dependent protease and in a gene encoding capsular polysaccharide biosynthesis protein resulted in abolished swarming suggesting that these proteins also play a potential role in the swarming activity of P. stutzeri E1. Keywords: Pseudomonas stutzeri, polycyclic aromatic hydrocarbon, phenanthrene, chemotaxis, plasposon pTnMod-OGm, swimming, swarming Title: Genetic analysis of phenanthrene-driven motility by the phenanthrene-degrading soil isolate Pseudomonas stutzeri E1 TóM TắT Pseudomonas stutzeri dòng E1 có khả năng di chuyển bề mặt tăng gấp đôi khi nuôi trong môi trường tối thiểu được phủ phenanthrene. Thí nghiệm mao dẫn cũng cho thấy E1 di chuyển nhanh gấp năm lần về hướng có phenanthrene. Plasposon pTnMod-OGm được dùng để tạo thư viện đột biến dòng E1. Trong số 2639 đột biến đã khảo sát, 82 đột biến biểu hiện những thay đổi về khả năng di chuyển theo phenanthrene và/hoặc phân hủy phenanthrene. 16 đột biến được chọn để giải trình tự của các gen đột biến tương ứng. Đột biến gen flhA làm E1 mất khả năng bơi và di chuyển bề mặt, đột biến gen flgK làm mất khả năng bơi và giảm khả năng di chuyển bề mặt của E1. Đột biến gen cheY làm mất khả năng bơi và giảm khả năng di chuyển bề mặt trong khi đột biến gen gidA làm giảm khả năng phân hủy phenanthrene và giảm cả khả năng bơi và di chuyển bề mặt của E1. Đột biến gen tổng hợp protein Zn-dependent protease và gen tổng hợp vỏ polysaccharide làm cho E1 mất khả năng di chuyển bề mặt chứng tỏ các protein này cũng giữ vai trò tiềm năng trong hoạt động di chuyển bề mặt của P. stutzeri E1. Từ khoá: Pseudomonas stutzeri, hydrocarbon đa vòng thơm, phenanthrene, hóa hướng động, plasposon pTnMod-OGm, bơi, di chuyển bề mặt